A collective intelligence oriented three-layer framework for socialized and collaborative product design. (1st July 2021) - Yang, Maolin; Li, Weidong; Jiang, Pingyu
Highlights: Collective intelligence oriented socialized product design. Blackboard model based alternative design solutions generation. Interval valued fuzzy VIKOR algorithm based consensus reaching. Support design practice in asynchronous, distributed, decentralized environment. Abstract: Socialized and collective intelligence oriented product design (SCPD) is a new kind of design pattern emerged under the context of advanced internet technologies and sharing economic trend. It is usually carried out by large numbers of socialized and self-driven participators from different social backgrounds in an open, sharing, self-organized, distributed, and collaborative manner. These characteristics bring SCPD with advantages such as rich design resources, high innovation potentials, deep connection with customer-centric markets, etc., but the characteristics also cause the problems of low efficiency and low reliability during the collaborative design process of SCPD. To mitigate these problems, a collective intelligence oriented three-layer SCPD framework is established. The first layer focuses on design task decomposition and subtask analysis. The second layer focuses on generating alternative design solutions for the subtasks using a customized Blackboard model. The third layer focuses on identifying the most preferred solution using a fuzzy VIKOR algorithm driven consensus reaching model. The SCPD framework is able to support orderly interaction, mutual inspiration, group decision making, and participation stimulation among the socialized participators. In this way, the framework provides a more systematic and efficient approach to utilize the CI from SPs for product design, and thus enlarges the application scope of SCPD pattern from software and small-scale physical products to relatively complicated and high-value physical products. The operability of the framework is demonstrated through an innovative 3D printer design project.